2010
DOI: 10.3945/jn.110.122499
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-Based Nutrient Supplement but Not Corn-Soy Blend Modestly Increases Weight Gain among 6- to 18-Month-Old Moderately Underweight Children in Rural Malawi

Abstract: Although widely used, there is little information concerning the efficacy of corn-soy blend (CSB) supplementation in the treatment of moderate underweight in African children. Lipid-based nutrient supplements (LNS), which have proven to be beneficial treatment for severely wasted children, could offer benefits to less severely affected individuals. We conducted a clinical randomized trial to determine whether LNS or CSB supplementation improves weight gain of moderately underweight children. A total of 182 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 21 publications
0
76
1
2
Order By: Relevance
“…The amount of weight gain improvement (120 g/12 weeks) was in the same direction but lower than weight gains reported when LNS has been offered for a similar duration in more controlled settings (150 g) (15) . Although the findings were statistically only marginally significant with or without adjustment for covariates, the effectiveness estimate is plausible in the context of the previous efficacy trials.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The amount of weight gain improvement (120 g/12 weeks) was in the same direction but lower than weight gains reported when LNS has been offered for a similar duration in more controlled settings (150 g) (15) . Although the findings were statistically only marginally significant with or without adjustment for covariates, the effectiveness estimate is plausible in the context of the previous efficacy trials.…”
Section: Discussionmentioning
confidence: 77%
“…In the current study, the incidence of any AE (diarrhoea, vomiting and skin rash) in the CSB and LNS groups was similar to that in the control group, a finding that others have documented from supplementary programmes (6) . However, a recent trial documented more episodes of vomiting and skin rash with LNS supplementation (15) . One reason for the difference might be because the current study was done in a less controlled setting such that some cases may not have been reported, unlike in the previous trial where the participants were visited weekly and encouraged to report to the hospital with any problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis of an RCT with 192 children 61 found that supplemented children who were more undernourished/ poorer gained significantly more weight than controls, but that feeding was ineffective for children with normal weights. One CBA 87 also found that children with low baseline WAZ gained more weight than controls while those whose WAZ was higher did not (n = 293).…”
Section: Poverty/child's Initial Nutritional Statusmentioning
confidence: 99%
“…Thakwalakwa 61 was the only RCT to receive ratings of low risk in all categories. Most of the other RCTs in LMIC received three 'low risk' ratings, while the other ratings were unclear, and a few were high risk.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%